MEMBANGUN MASYARAKAT MELALUI KEARIFAN LOKAL BUDAYA BIMA “LAMBA ANGI” - Hasan Ali (Universitas Hasanuddin, 2021)
The culture of a nation or a group of people is a reflection of the concepts of the life order of a society. The elements of a culture that is owned by a society sometimes change because not passed on continuous from generation to generation. The modification galloping changes that appear on order of life of the people that dynamic. As soon as that happens in people society of Bima. Habits are performed by the elders are already entrenched in the life of society, sometimes not continues by generations today, like culture lamba angi ' relationship ' with family or relatives.